Durable Antibacterial Finishing on Organic Cotton by Inclusion of Thymol into Cyclodextrin Derivative - M. Sundrarajan; A. Rukmani (E-Journal of Chemistry)
Antibacterial finish was done on organic cotton by incorporation of thymol into monochlorotriazinyl-β-cyclodextrin. Fabric was modified with cyclodextrin derivative in alkaline condition. UV-Visible and FT-IR studies confirmed the presence of cyclodextrin derivative and thymol on modified fabric. The level of thymol entrapped into the fabric was determined quantitatively by HPLC analysis. Agar diffusion test was carried for unwashed and washed fabric against gram positive (S. aureus) and gram negative (E. coli) bacteria. The investigation revealed that modification of fabric with monochlorotriazinyl-β-cyclodextrin retained the antibacterial property even after 10 washing process.